2016
DOI: 10.1097/bot.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Acute Hand Care in the Southwest United States

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Many studies have demonstrated that patients presenting with hand injuries to an emergency department often do not require a hospital admission. 1,3,15,16,39,40 Despite this trend, a large number of patients were still found to undergo imaging studies and specialty consultation. 15,40 Most patients were treated and discharged from an emergency department, indicating that many can be managed in a clinic setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have demonstrated that patients presenting with hand injuries to an emergency department often do not require a hospital admission. 1,3,15,16,39,40 Despite this trend, a large number of patients were still found to undergo imaging studies and specialty consultation. 15,40 Most patients were treated and discharged from an emergency department, indicating that many can be managed in a clinic setting.…”
Section: Discussionmentioning
confidence: 99%
“…15,40 Most patients were treated and discharged from an emergency department, indicating that many can be managed in a clinic setting. 3…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical treatment of hand infections is complex and challenging due to the intricate anatomy involved, the low tolerance for adhesions, and the potential for long-term morbidity. They serve as a common etiology for emergency department admissions 1 and tend to occur in younger males (median age 36e40), with as much as 89% male predominance. 1e3 Because of the impact on patient lifestyle, executive function, and survival, appropriate treatment must be given in a timely manner.…”
Section: Introductionmentioning
confidence: 99%